Synthesis of highly selective spherical caffeine imprinted polymers via ultrasound-assisted precipitation polymerization - Phutthawong,N. (John Wiley and Sons Inc., 2015)
© 2012 Wiley Periodicals, Inc. A facile and efficient method for synthesis of molecularly imprinted polymers via ultrasound-assisted precipitation polymerization was developed. Caffeine was applied as a model template in the imprinting using methacrylic acid and ethylene glycol dimethacrylate as a functional monomer and a crosslinker, respectively. Polymerization under sonochemical conditions proceeded rapidly (within 3 h at 60°C) to afford polymer microspheres with narrow size distributions in excellent yields while maintaining the binding specificity toward the template. It was found that the imprinted polymer prepared at low initial temperature (40°C) exhibited the best caffeine binding performance in terms of specificity and selectivity.